Old v New Politics in Malaysia: State and Society in Transition edited by Francis Loh Kok Wah, Petaling Jaya: SIRD and Penang: Aliran Kesedaran Negara, 2009, 316 pp. - Wong Chin Huat, (Kajian Malaysia, 2010)
A collection of articles published in the Penang-based political commentary magazine Aliran Monthly, a local business magazine (Malaysian Business) and two foreign publications (Australian Society and the ACHRO book), the book does not offer any grand theory to explain the transition nor any prediction of what may follow. Published in the first half of 2009, it does not cover the cow-head protest days before the National Day that year and the Allah row which led to arson of churches and mosques in the following January. It however gives a detailed account of Muslim-Hindu conflict in Kampung Rawa, Penang over a Hindu Temple in 1998, an incident before the Reformasi movement forgotten by most. This example exactly illustrates the merit and value of the book. It is a reminder how Malaysia has come to where it is today. Reading the past and comparing it to the present allow one to see both the constants and variables as well as both challenges and hopes in Malaysia’s society and politics.